2008
DOI: 10.1002/art.24008
|View full text |Cite
|
Sign up to set email alerts
|

A 36‐year‐old man with paresthesias and a headache

Abstract: History of the present illnessA 36-year-old man with a history of non-Hodgkin's lymphoma was admitted to the hospital with paresthesias and a headache. His paresthesias began 5 months prior to admission, when he developed left leg numbness and pain, accompanied by an erythematous rash that he described as "splotchy." The rash appeared initially on the patient's left leg, but then expanded to include his torso and upper extremities. The rash, numbness, and pain all resolved without intervention after 1 week. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…In vitro studies using fibroblasts derived from either Smad2-or 3-null embryos have revealed a complex picture of TGF-b1 transcriptional regulation, indicating distinct mechanisms of TGF-b1 gene regulation by Smad2, Smad3 or both (19). Castelino et al (11) demonstrated a pathological role of LPA 1 receptor in dermal fibrosis. Using a scleroderma model, Castelino reported a reduction in dermal fibrosis, a-SMA-positive cells and phospho-Smad2-positive cells in LPA 1 knockout mice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In vitro studies using fibroblasts derived from either Smad2-or 3-null embryos have revealed a complex picture of TGF-b1 transcriptional regulation, indicating distinct mechanisms of TGF-b1 gene regulation by Smad2, Smad3 or both (19). Castelino et al (11) demonstrated a pathological role of LPA 1 receptor in dermal fibrosis. Using a scleroderma model, Castelino reported a reduction in dermal fibrosis, a-SMA-positive cells and phospho-Smad2-positive cells in LPA 1 knockout mice.…”
Section: Discussionmentioning
confidence: 99%
“…LPA levels were elevated in serum of SSc compared with serum of healthy controls (9), and fibroblasts cultured from SSc skin showed a significant increase of LPA-activated chloride channel current activity following LPA exposure compared with control skin fibroblasts (10). Also, the role of LPA has been demonstrated in several animal models of organ fibrosis (11)(12)(13)(14)(15). In a renal fibrosis model using unilateral ureteral obstruction, tubulointerstitial fibrosis was reduced in LPA 1 receptor knockout mice (14).…”
Section: Introductionmentioning
confidence: 99%